INTERPERSONAL MEANING OF MODALITY IN UNDERGRADUATE THESES OF ENGLISH DEPARTMENT: A SYSTEMIC FUNCTIONAL GRAMMAR APPROACH (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
Modality is a key in articulating the authors' viewpoints in their arguments. To address the gap, this recent study aims to thoroughly describe the interpersonal meaning in terms of modality within English Literature’s undergraduate theses. Textual analysis using a corpus-based approach was rigorously applied. This research utilized AntConc 4.2.0 version as instrument. The researcher meticulously selected 40 undergraduate theses between March and August 2023. The SFL concept proposed by Halliday and Matthiessen (2004) was implemented to analyze the data. The findings demonstrated that undergraduate students largely used modalization in the context of probability across the undergraduate theses. It indicates that they utilize the modality to persuade readers by describing upcoming developments and exchanging information with them. Undergraduate students additionally employed medium modality with greater frequency than low modality. It indicates that they perceive the readers as having the same status as others, which promotes a peaceful relationship between them. It suggests that undergraduate students intentionally become involved with the readers through the ideas presented in the undergraduate theses, harmonizing their positions of authority with the readers, leading to a warm connection between them. Thus, it reflects the close distance between conversational participants.